Reactive Vasodilation Predicts Mortality in Primary Systemic Light-Chain Amyloidosis. Issue 8 (27th September 2019) - Stamatelopoulos, Kimon; Georgiopoulos, Georgios; Athanasouli, Fani; Nikolaou, Panagiota-Efstathia; Lyka, Marita; Roussou, Maria; Gavriatopoulou, Maria; Laina, Aggeliki; Trakada, Georgia; Charakida, Marietta; Delialis, Dimitris; Petropoulos, Ioannis; et al.
Abstract : Rationale: : Cardiac involvement and hypotension dominate the prognosis of light-chain amyloidosis (AL). Evidence suggests that there is also peripheral vascular involvement in AL but its prognostic significance is unknown. Objective: : To evaluate vascular dysfunction in patients with AL as a potential future area of intervention, we assessed the prognostic utility of flow-mediated dilatation (FMD), a marker of vascular reactivity, which is augmented under conditions of hypotension and autonomic dysfunction. Methods and Results: : We prospectively evaluated 115 newly diagnosed untreated AL patients in whom FMD was measured. FMD in AL patients was significantly higher than age-, sex- and risk factors–matched controls (4.0% versus 2.32%; P =0.006) and comparable with control groups at lower cardiovascular risk ( P >0.1). Amyloidosis patients presented increased plasma and exhaled markers of the NO pathway while their FMD significantly correlated with augmented sustained vasodilatation after sympathetic stimulation. Increased FMD (≥4.5%) was associated with early mortality (hazard ratio, 4.36; 95% CI, 1.41–13.5; P =0.010) and worse survival (hazard ratio, 2.11; 95% CI, 1.17–3.82; P =0.013), even after adjustment for Mayo stage, nerve involvement and low systolic blood pressure. This finding was confirmed in a temporal validation AL cohort (n=55; hazard ratio, 4.2; 95% CI, 1.45–12.3; P =0.008). FMD provided significant reclassification value over the best prognostic model (continuous Net Reclassification Index, 0.61; P =0.001). Finally, better hematologic response was associated with lower posttreatment FMD. Conclusions: : FMD is relatively increased in AL and independently associated with inferior survival with substantial reclassification value. Reactive vasodilation merits further investigation as a novel risk biomarker in AL.Visual Overview: An online visual overview is available for this article. Abstract : Supplemental Digital Content is available in the text.